PENGARUH MODEL DISCOVERY TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV - Windhi, Windhi; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to analyze the effect of discovery models on learning outcomes in the thematic learning of Grade IV 55 Primary Schools in West Pontianak. The method used is an experimental method. In this study, researchers used a quasi-experimental design, with the form of nonequivalent control group design. The population of this research is all of class IV 55 Pontianak Elementary School. The sample was determined using a total sampling technique and obtained a sample of IVB class totaling 30 students as an experimental class and IVA totaling 25 students as a control class. Data collection techniques using measurement techniques. Data collection tools in the form of multiple choice tests housed 45 questions. The results showed that the average post-test of the experimental class and the average post-test of the control class, obtained a tcount of 0.769 with dk = 30 + 25-2 = 53 with a significant level (Î±) = 5% obtained a table of 2.007, because t count is 0.769> t table equal to 2.007 then Ha is accepted, so it can be concluded that there is an influence of discovery models on learning outcomes in the thematic learning of class IV 55 Primary Schools in West Pontianak. Based on the results of the calculation of the effect size (ES) obtained ES = 0,59 which includes the criteria of being. This means that the discovery model has a moderate effect on learning outcomes in the thematic learning of Grade IV 55 Primary Schools in West Pontianak.Â Keywords: Discovery Model, Influence, Learning Outcomes.